Mechanochromic Switches: A Supramolecule‐Triggered Mechanochromic Switch of Cyclodextrin‐Jacketed Rhodamine and Spiropyran Derivatives (Adv. Funct. Mater. 3/2016). (18th January 2016) - Wan, Shulin; Ma, Zhiyong; Chen, Chen; Li, Fangfei; Wang, Feng; Jia, Xinru; Yang, Wantai; Yin, Meizhen
Abstract : Covalent bond‐activated mechanoresponse in a supramolecule‐triggered mechanochromic switch is reported by M. Yin and co‐workers on page 353, through complexing rhodamine or spiropyran with cyclodextrin (CD). The strong hydrogen bonds provided by CD play a crucial role in triggering the mechanochromic switch. Unique characteristics such as noncovalent chemical modification and convenient preparation make this approach promising for practical applications.